Prof. Dr. Stefan Ouma and Dr. Faisal Garba Muhammed on mobility and the need for a macrosociology in/of Africa - Ouma, Stefan; Muhammed, Faisal Garba (Cluster Conversations, 2023)
In this latest episode of the Cluster Conversations fellow Dr. Faisal Garba Muhammed talks with his fellowship host Prof. Dr. Stefan Ouma about his research project in which he scrutzinizes datasets on mobility in Africa that he collected for almost 20 years. They also explore the need for a macrosociology in/of Africa.